أثر التطورات الاقتصادية والتكنولوجية على المبادئ التعاقدية - منصور، عصام (المصطفى الغشام الشعيبي, 2023)
لقد أدت التحولات الاقتصادية والتكنولوجية إلى فرض العديد من التحديثات التي مست بشكل مباشر الأسس التقليدية في العقد وفي مقدمتها أعرق مبدأي مبدأ القوة الملزمة، ومبدأ سلطان الإرادة، فهذه التطورات أدت إلى حياكة نظم قانونية جديدة أثرت بشكل مباشر، أو غير مباشر على مبدأ القوة الملزمة بحيث أدت إلى التخفيف من حدة هذا المبدأ وقلصت بشكل واضح من صرامته والذي ظلت التشريعات عاجزة أمامه لوقت طويل. بحيث ظهرت نظريات تؤثر بشكل كبير على أثار هذا المبدأ لعل أهم هذه النظريات نظرية إنقاذ العقد والذي ظهرت في التشريع والفقه الألماني والتي تنادى باستعمال كافة الطرق المتاحة والمشروعة بهدف إنقاذ العقد، وتسمح للطرفين والغير والقاضي والمشرع على حد سواء التعديل في العقد بهدف إنقاذه والإبقاء عليه وهو الشيء المخالف للمبادئ القوة الملزمة والتي لا ترضى بأي تدخل يكون خارجا عن نطاق أطراف العلاقة التعاقدية وتحظر المساس بالعقد والتعدي على قدسيته. The economic and technological transformations have led to the imposition of many updates that directly affected the traditional foundations of the contract, foremost of which are the oldest principles of the principle of binding force, and the principle of the authority of the will. These developments led to the weaving of new legal systems that directly or indirectly affected the principle of force. Binding, which led to the mitigation of this principle and clearly reduced its strictness, in front of which legislation remained powerless for a long time. So that theories have appeared that greatly affect the effects of this principle, perhaps the most important of these theories is the theory of saving the contract, which appeared in German legislation and jurisprudence, which calls for the use of all available and legitimate methods in order to save the contract, and allows both parties and third parties, the judge and the legislator alike, to amend the contract in order to save and maintain it. The thing that contradicts the principles of the binding force, which is not satisfied with any interference that is outside the scope of the parties to the contractual relationship and prohibits prejudice to the contract and the violation of its sanctity.
Keywords: الالتزامات العقدية -- القانون المدني -- التصرف القانوني -- الأوضاع الاقتصادية -- حماية المستهلك